Behind road sign name with Jawi / Fauzi Harun - Harun, Fauzi (Faculty of Art and Design, Universiti Teknologi MARA Melaka, Alor Gajah Campus, 2014)
History of Jawi: Jawi script presence to the Malay world is directly linked with the coming of Islam to the archipelago where at that time, not only in the area of literature such as writing were developed but also, types of music, dances and costumes as well (Amran Kasimin, 1993).